Stabilization for a degenerate wave equation with drift and potential term with boundary fractional derivative control - Ibtissam Issa; Zayd Hajjej (Electronic Research Archive)
This paper explores the boundary stabilization of a degenerate wave equation in the non-divergence form, which includes a drift term and a singular potential term. Additionally, we introduce boundary fractional derivative damping at the endpoint where divergence is absent. Using semi-group theory and the multiplier method, we establish polynomial stability, with a decay rate depending upon the order of the fractional derivative.